Different cell types in Neurospora crassa - George N. Bistis; David D. Perkins; Nick D. Read (Fungal Genetics Reports, 2003)
Neurospora possesses more cell types than are commonly recognized. We have been able to identify 28 morphologically distinct types. Having the cell types clearly defined will be important for genome annotation, describing new mutant phenotypes, and determining sites of gene expression.